COMPARATIVE STUDY OF ORGANIZATIONAL COMMITMENT AMONG GENERATION X AND GENERATION Y THROUGH ANALYSIS OF DIFFERENCES IN THE INFLUENCE OF EMPOWERMENT AND VALUE: Empirical Study using Ex-Post Facto Variables on State-Owned Bank Employees in South Jakarta - Adiawaty, Susi; Moeins, Prof. Dr. Anoesyirwan; Sunaryo, Dr. Widodo (UTSAHA: Journal of Entrepreneurship, 2024)
The differences in the character of generation X and generation Y in terms of the way of working, the values they have, and their commitment to the organization are matters that must be addressed by the company during the development of the banking world, especially state-owned banks in the face of changes in the company’s external environment in the future. This is a comparative research that aims to identify differences in organizational commitment between generation X and generation Y through the influence of empowerment and value. The research findings indicate significant differences between organizational commitment in generations X and Y. In the dimensions of affective commitment, normative commitment, and continuance commitment, significant differences were found between them. Empowerment and value have a significant influence on organizational commitment in generation X, with a significant joint influence. Similar is the case for generation Y, with a lower level of influence. The analysis revealed that the determination of empowerment in generation X was higher than that in generation Y, while differences in the contribution of value’s influence were also observed between the two generations. Qualitative tests using the Delphi technique also support these quantitative findings.